Polysaccharide composition of fraxinus angustifolia leave infusions - Martins, Vitor Manuel Ramalheira (2011)
The use of plants with medicinal purposes is an ancient practice, which is still very common all around the world and that has been largely increasing over the last decades. Data from the World Health Organization indicate that 80% of the total human population still treat their health problems with traditional remedies [1]. Consequently, a large number of ethnobotanical research studies focused on the flora of diverse countries can be found in the literature [1,2]. According to these ethnobotanical studies, the infusion is one of the most frequently cited preparation processes. The infusions of “freixo“ (Fraxinus angustifolia) dried leaves protects against high levels of cholesterol, blood pressure, and uric acid, and act against rheumatism [3]. These health benefits are associated with the presence of several physiologically active substances, such as phenolic compounds, essential oils, and polysaccharides, among others [4]. Although phenolic compounds have been studied in detail for more than two decades, the characterization of the polysaccharides present in plant´s infusions and their involvement in the health benefits is still incipient. The aim of this work is to provide a first insight into the polysaccharide composition of the infusions from Fraxinus angustifolia dried leaves.